Chemical Composition and Biological Activity of Essential Oil Extracted from the Aerial Part of Elsholtzia fruticosa against Ditylenchus destructor. Issue 3 (3rd May 2020) - Liang, Jun-yu; Ning, An-qi; Lu, Pei-yu; Shao, Ya-zhou; Xu, Jie; Yang, Ying-Ying; Wang, Hong-li
Abstract: The present study investigated the chemical composition of essential oil extracted from Elsholtzia fruticosa, and evaluated the biological activities of the essential oil and its main components against Ditylenchus destructor . The essential oil of E. fruticosa was obtained by hydrodistillation and analyzed by GC/ MS. Twenty-three components of essential oil were identified. The most abundant compounds were eucalyptol (40.1%), γ-terpinene (15.8%), limonene (9.3%) and β-pinene (5.2%). Essential oil and three major constituents (eucalyptol, γ-terpinene, and limonene) were tested for their biological activities against D. destructor . The results showed that the essential oil, eucalyptol, γ-terpinene, and limonene exhibited a strong effect of suppression against D. destructor (EC50/24h  = 0 .16, 0.27, 0.36 and 0.23 mg/ml, respectively). The essential oil, eucalyptol, ã -terpinene, and limonene also possessed the obvious nematicidal activities against D. destructor (LC50/24h  = 0 .18, 0.46, 0.66 and 0.38 mg/ml, respectively). The essential oil and main components described herein merit further study as potential botanical nematicides against D. destructor .